Respuesta :
3x - y = 6
3x = 6 + y
y = 3x - 6, slope = 3
Y = 3x + b
-6 = 3(-4) + b
-6 = -12 + b, b = 6
Solution: y = 3x + 6
3x = 6 + y
y = 3x - 6, slope = 3
Y = 3x + b
-6 = 3(-4) + b
-6 = -12 + b, b = 6
Solution: y = 3x + 6
Answer:
the desired equation is 3x - y = -6
Step-by-step explanation:
Recall that parallel lines have the same slope. Thus, the desired line has an equation of the form 3x - y = C, where C is determined by the coordinates of the point (-4, -6).
3x - y = C becomes 3(-4) - (-6) = C after substitution of -4 and -6 for x and y respectively. Then -12 + 6 = C, and C = -6.
Thus, the desired equation is 3x - y = -6